2018
DOI: 10.1158/1940-6207.capr-17-0230
|View full text |Cite
|
Sign up to set email alerts
|

Does Mutated K-RAS Oncogene Attenuate the Effect of Sulindac in Colon Cancer Chemoprevention?

Abstract: The NSAID sulindac has been successfully used alone or in combination with other agents to suppress colon tumorigenesis in patients with genetic predisposition and also showed its efficacy in prevention of sporadic colon adenomas. At the same time, some experimental and clinical reports suggest that a mutant oncogene may negate sulindac antitumor efficacy. To directly assess sulindac activity at suppressing premalignant lesions carrying K-RAS mutation, we utilized a novel mouse model with an inducible colon-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The clinical impact of prevention agent combinations is illustrated by the breakthrough trial sulindac and erlotinib, which reduced the occurrence of duodenal adenomas (104)(105)(106). Recent transcriptomic and other correlative science studies from this landmark-positive randomized trial in FAP identified molecular targets and innate immune pathways mediating sulindac-erlotinib suppression of duodenal polyposis; and Kras mutations attenuated sulindac efficacy in mouse models, with implications for precision prevention (107).…”
Section: State Of Cancer Prevention Sciencementioning
confidence: 99%
“…The clinical impact of prevention agent combinations is illustrated by the breakthrough trial sulindac and erlotinib, which reduced the occurrence of duodenal adenomas (104)(105)(106). Recent transcriptomic and other correlative science studies from this landmark-positive randomized trial in FAP identified molecular targets and innate immune pathways mediating sulindac-erlotinib suppression of duodenal polyposis; and Kras mutations attenuated sulindac efficacy in mouse models, with implications for precision prevention (107).…”
Section: State Of Cancer Prevention Sciencementioning
confidence: 99%
“…KRAS is the prototype molecule family as canonical player in constituting further evolution in cell adaptability and response. Screening for K-RAS gene mutations is important in patients with colon polyps to thus provide possible personalised interventions targeting mutant K-RAS signaling pathways [11] .…”
Section: Compartmentalizationmentioning
confidence: 99%